An appressorium membrane protein, Pams1, controls infection structure maturation and virulence via maintaining endosomal stability in the rice blast fungus - Wang, Jing; Wang, Qing; Huang, Pengyun; Qu, Yingmin; Huang, Zhicheng; Wang, Huan; Liu, Xiao-Hong; Lin, Fu-Cheng; Lu, Jianping (Frontiers in Plant Science, 2022)
The rice blast fungus Magnaporthe oryzae spores differentiate and mature into functional appressoria by sensing the host surface signals. Environmental stimuli are transduced into cells through internalization during appressorium formation, like in the cAMP-PKA pathway. Here we describe a novel contribution to how appressoria mature on the surface of a leaf, and its connection to endosomes and the cAMP-PKA pathway. An appressorium membrane-specific protein, Pams1, is required for maintaining endosomal structure, appressorium maturation, and virulence in M. oryzae. During appressorium development, Pams1 was translocated from the cell membrane to the endosomal membrane. Deletion of PAMS1 led to the formation of two types of abnormal appressoria after 8 hours post inoculation (hpi): melanized type I had a reduced virulence, while pale type II was dead. Before 8 hpi, Δpams1 formed appressoria that were similar to those of the wild type. After 8 hpi, the appressoria of Δpams1 differentiated into two types: (1) the cell walls of type I appressoria were melanized, endosomes were larger and had a different distribution from the wild type, and (2) Type II appressoria gradually stopped melanization and began to die. The organelles, including the nucleus, endosomes, mitochondria, and endoplasmic reticula, were degraded, leaving only autophagic body-like vesicles in these appressoria. Addition of exogenous cAMP to Δpams1 led to formation of a greater proportion of type I appressoria and a smaller proportion of type II appressoria. Thus, defects in endosomal structure and the cAMP-PKA pathway are among the causes of the defective appressorium maturation and virulence of Δpams1.